Double-faced adhesive tape-like viscous polymer solid electrolyte membrane and preparation method thereof
Through the design and preparation of double-sided adhesive-like adhesive polymer solid electrolyte membrane, the low conductivity of polymer electrolytes in solid-state batteries and the safety performance of gel electrolytes are solved, and efficient bonding and performance improvement of lithium-ion batteries are achieved. .
Patent Information
- Application Number
- CN202411649622.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-14
AI Technical Summary
In the current solid-state battery technology, polymer solid-state batteries have insufficient ionic conductivity, making practical progress difficult, and gel electrolytes have safety performance problems.
A double-sided adhesive-like adhesive polymer solid electrolyte membrane is used, which is formed by a composite of the polymer porous membrane with an ionic conductivity polymer, lithium salt and ionic liquid, and the viscosity and conductivity of the membrane are improved by a specific preparation method.
It improves the conductivity and viscosity of lithium-ion batteries, reduces interface resistance, simplifies production processes, and improves the safety and production efficiency of batteries.
Smart Images

Figure CN119447443A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a double-sided adhesive type viscous polymer solid electrolyte membrane and a preparation method thereof. Background Art
[0002] The current solid-state battery technology is divided into inorganic solid-state battery route and polymer solid-state battery route. Among them, the electrolyte of inorganic solid-state battery is mainly oxides and sulfides, with high ionic conductivity, but high brittleness, high interface resistance and poor stability. The polymer technology route can make up for the shortcomings of the inorganic electrolyte route, but the ionic conductivity of the all-solid-state polymer electrolyte is insufficient, and it is difficult to make practical progress. Although the ionic conductivity of the gel electrolyte can reach the level of liquid electrolyte, there are still a large number of flammable small molecule organic solvents, and the safety performance has been criticized. Therefore, the current development of the solid-state battery technology route is not perfect, and it is necessary to develop an electrolyte membrane with better comprehensive performance to solve its existing problems. Summary of the invention
[0003] The purpose of the present invention is to provide a double-sided tape-type adhesive polymer solid electrolyte membrane and a preparation method thereof in response to the problems and shortcomings of current solid electrolytes, which can improve the ionic conductivity of the polymer electrolyte, reduce the interface resistance, and obtain an electrolyte membrane with double-sided tape-like adhesion, provide a new bonding preparation process for lithium-ion batteries, and simplify the current lithium battery production process.
[0004] The technical solution of the present invention is achieved in this way:
[0005] The double-sided tape-like viscous polymer solid electrolyte membrane described in the present invention has the following characteristics: the membrane body is formed by a composite of a polymer porous membrane and an ion-conductive polymer, a lithium salt, and an ionic liquid, that is, the electrolyte membrane uses a polymer porous membrane as a matrix, and the surface and pores of the matrix are covered with a copolymer layer formed by an ion-conductive polymer, a lithium salt, and an ionic liquid.
[0006] The method for preparing the double-sided adhesive type adhesive polymer solid electrolyte membrane of the present invention is characterized by comprising the following steps:
[0007] (1) dissolving an ion conductive polymer and a lithium salt in an organic solvent at a certain molar ratio to prepare a solution A;
[0008] (2) adding an appropriate amount of ionic liquid to solution A and stirring for a certain period of time to obtain a uniform solution B;
[0009] (3) adding solution B to a polymer porous membrane having a certain thickness to fully infiltrate the membrane;
[0010] (4) The polymer porous membrane fully soaked with solution B is dried by air blowing for a period of time, and then dried under vacuum to obtain a double-sided adhesive-type adhesive polymer solid electrolyte membrane for lithium-ion batteries.
[0011] Furthermore, the ion conductive polymer described in step (1) is one or more of polyether, polycarbonate, polyurethane, polysiloxane, and polyphosphate.
[0012] Furthermore, the lithium salt described in step (1) is one or more of lithium chloride, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), and lithium bis(trifluoromethylsulfonylimide).
[0013] Furthermore, the molar ratio described in step (1) is the molar ratio of the structural unit of the ion conductive polymer to the lithium salt, ranging from (5 to 40):1; and the mass concentration of the ion conductive polymer is 0.01 to 0.2 g / mL.
[0014] Furthermore, the organic solvent described in step (1) is one or more of acetonitrile, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethanol, methanol, carbon tetrafluoride, ethylene glycol, propionitrile, tributyl phosphate, chloroform, and ethyl acetate.
[0015] Furthermore, the adding of an appropriate amount of ionic liquid in step (2) refers to the addition of the ionic liquid and the ion conductive polymer in a mass ratio of (1 to 5):1; and the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, 1,3-bis(cyanomethyl)imidazolium chloride, 1,3-bis(cyanomethylimidazolium bis(trifluoromethylsulfonyl)imide, 1,3-bis(cyanomethyl)imidazolium bis(pentafluoroethylsulfonyl)imide, 1-cyanomethyl-3-methylimidazolium chloride, 1-cyanomethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-3-methylimidazolium tricyanomethyl salt, 3-cyanopyridine hydrogen sulfate, 1,10 -phenanthroline dihydrogensulfate, 1-methyl-3-ethylimidazole dicyanamide, 3-methyl-1-butylpyridine dicyanamide, 1-butyl-3-methylimidazole dihydrogenphosphate, 1-hexyl-3-methylimidazole dicyanamide, 1-butyl-3-methylimidazole hydrogensulfate, 1-ethyl-3-methylimidazole tetrafluoroborate, 1-methyl-3-hexadecylimidazole tetrafluoroborate, poly (1-butyl-4-vinylpyridine dicyanamide), polymeric p-phenylenediamine sulfate, 1-ethyl-3-methylimidazole dicyanamide, 1-cyano-3-methylimidazolyl chloride, 1-butyl-3-methylimidazole tetrachloroferrate, N,N-dimethyl-N-formyl ammonium bis (trifluoromethylsulfonyl) imide, 1-butyl-3-methylimidazole tetrafluoroborate or more.
[0016] Furthermore, the stirring time in step (2) is 5 to 24 hours.
[0017] Furthermore, the polymer porous membrane described in step (3) can be prepared by electrospinning, melt spinning, phase inversion, stretching or thermally induced phase separation, and the matrix material of the polymer porous membrane is one or more of polyethylene, polypropylene, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, polyurethane, polyetheretherketone, polyimide, polyaniline, polystyrene, polyglycolic acid, polylactic acid, polycaprolactone and polyamide.
[0018] Furthermore, the thickness of the polymer porous membrane in step (3) is 10 to 300 μm.
[0019] Furthermore, the blast drying temperature in step (4) is 25-100° C., and the drying time is 1-12 h; the vacuum drying temperature is 60-120° C., and the drying time is 12-48 h.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The electrolyte membrane of the present invention has excellent viscosity, can efficiently bond positive and negative electrode materials, effectively avoid the problem of positive and negative electrode displacement, has high safety, and provides a new bonding preparation process for lithium-ion battery preparation, simplifies the traditional lithium-ion battery process, greatly improves the production efficiency of the battery, and reduces the production cost of lithium-ion batteries;
[0022] 2. The viscosity of the electrolyte membrane of the present invention comes from the reversible intermolecular force. When the battery cell inside is damaged, the damaged electrode or electrolyte part can be peeled off, so that the battery cell can be quickly repaired;
[0023] 3. The viscosity of the electrolyte membrane of the present invention can reduce the interface resistance between the electrode and the electrolyte membrane and improve the performance of the lithium-ion battery;
[0024] 4. The electrolyte membrane of the present invention has good chemical stability, high room temperature ionic conductivity, and integrates a porous membrane three-dimensional network skeleton, giving the membrane sufficient mechanical properties and strong mechanical properties, and can be prepared into a room temperature solid-state battery;
[0025] 5. The raw materials used in the electrolyte membrane of the present invention, such as ion-conductive polymers, lithium salts, ionic liquids and porous membranes, have been industrialized, are cheap and have a wide variety. The corresponding electrolyte membrane can be obtained by simple compounding, and is easy to mass-produce;
[0026] 6. The performance of the electrolyte membrane of the present invention is controllable, controlled by the porous membrane skeleton, the shape and size are stable and controllable, the mechanical strength is high, and it is flexible;
[0027] 7. The viscose electrolyte membrane of the present invention has the characteristics of being non-flammable, non-leaking, highly stable and having good safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the preparation process of the present invention.
[0029] Figure 2 Schematic diagram of the structure of the electrolyte membrane of the present invention
[0030] Figure 3 This is a schematic diagram of the change of ionic conductivity with temperature in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] Embodiment 1:
[0032] (1) dissolving an ion conductive polymer and a lithium salt in an organic solvent at a molar ratio of 18:1, wherein the ion conductive polymer is polyethylene oxide, which is a type of polyether, the lithium salt is lithium bistrifluoromethylsulfonyl imide, and the organic solvent is an acetonitrile solution, maintaining the mass concentration of polyethylene oxide at 0.05 g / mL, and stirring for 6 hours to obtain a uniform solution A;
[0033] (2) adding ionic liquid to solution A at a mass ratio of 1.5:1, and stirring for 5 h to form a fully uniform solution B, wherein the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt;
[0034] (3) adding solution B to a polymer porous membrane with a thickness of 100 μm to fully infiltrate the membrane; the polymer porous membrane is prepared in advance, specifically, polyacrylonitrile is dissolved in N,N-dimethylformamide, the solid content of the solution is controlled to be 8%, and a 100 μm polyacrylonitrile porous membrane is prepared by electrospinning;
[0035] (4) The polyacrylonitrile porous membrane fully soaked with solution B was placed in a forced air oven and dried at 30°C for 2 h, and then transferred to a vacuum oven and dried at 60°C for 24 h to obtain a double-sided adhesive type adhesive polymer solid electrolyte membrane. The ionic conductivity test results are as follows: Figure 3 As shown in Figure 2, it can be seen that the membrane ionic conductivity increases with increasing temperature and reaches 10 -3 The level of S / cm indicates that it can be used normally at room temperature.
[0036] Embodiment 2:
[0037] (1) dissolving an ion conductive polymer and a lithium salt in an organic solvent at a molar ratio of 10:1, wherein the ion conductive polymer is polycarbonate, the lithium salt is lithium perchlorate, and the organic solvent is an acetone solution, maintaining the mass concentration of the polycarbonate at 0.08 g / mL, and stirring for 12 hours to obtain a uniform solution A;
[0038] (2) adding ionic liquid to solution A in a mass ratio of 1:1 and stirring for 6 h to form a fully uniform solution B, wherein the ionic liquid is 1,3-bis(cyanomethylimidazole bis(trifluoromethylsulfonyl)imide salt;
[0039] (3) adding solution B to a polymer porous membrane having a thickness of 25 μm to fully infiltrate the membrane; the polymer porous membrane is prepared in advance, specifically, a 25 μm polypropylene porous membrane is prepared by melt spinning polypropylene;
[0040] (4) The polypropylene porous membrane fully soaked with solution B is placed in a forced air oven and dried at 30°C for 1 hour, and then transferred to a vacuum oven and dried at 60°C for 24 hours to obtain a double-sided adhesive-type adhesive polymer solid electrolyte membrane.
[0041] Embodiment 3:
[0042] (1) dissolving an ion conductive polymer and a lithium salt in an organic solvent at a molar ratio of 20:1, wherein the ion conductive polymer is polypropylene oxide, which is a type of polyether, the lithium salt is lithium hexafluorophosphate, and the organic solvent is an acetone solution, maintaining the mass concentration of polypropylene oxide at 0.08 g / mL, and stirring for 5 hours to obtain a uniform solution A;
[0043] (2) adding ionic liquid to solution A at a mass ratio of ionic liquid to polyethylene oxide of 2:1, and stirring for 8 hours to form a fully uniform solution B, wherein the ionic liquid is N,N-dimethyl-N-formyl ammonium bis(trifluoromethylsulfonyl)imide;
[0044] (3) adding solution B to a polymer porous membrane with a thickness of 100 μm to fully infiltrate it; the polymer porous membrane is prepared in advance, specifically, polyamic acid is dissolved in N,N-dimethylacetamide, the solid content of the solution is controlled to be 10%, and a polyamic acid porous membrane with a thickness of 100 μm is first obtained by electrospinning, and then thermal imidization is performed at 300° C. for 2 h to obtain a polyimide porous membrane;
[0045] (4) The polyimide porous membrane fully soaked with solution B is placed in a forced air oven and dried at 30° C. for 1 h, and then transferred to a vacuum oven and dried at 80° C. for 48 h, thereby obtaining a double-sided adhesive-type adhesive polymer solid electrolyte membrane.
[0046] Comparative Example 1:
[0047] The preparation method is similar to that of Example 1, except that no ionic liquid is added.
[0048] Comparative Example 2:
[0049] The membrane is formed by solution casting with polyethylene oxide, lithium salt and ionic liquid in the proportions of Example 1 without a polymer porous membrane as support.
[0050] Table 1 is a performance parameter comparison table of Examples 1-3 and Comparative Examples 1-2.
[0051] Table 1 Electrolyte membrane performance parameter comparison table
[0052]
[0053] As can be seen from Table 1, since no ionic liquid is added in Comparative Example 1, the electrolyte membrane obtained is not sticky and has a large impedance. Since Comparative Example 2 is formed by a solution casting method, there is no polymer porous membrane as a support, so the membrane strength is low and there is deformation. It can be seen that the electrolyte membrane formed by a polymer porous membrane and an ion conductive polymer, a lithium salt, and an ionic liquid can reduce the interface resistance between the electrode and the electrolyte membrane, improve the performance of the lithium ion battery, and the performance is controllable. It is controlled by the porous membrane skeleton, the shape and size are stable and controllable, the mechanical strength is high, and it is also flexible.
[0054] In addition, according to the actual preparation conditions, in other embodiments, the ion conductive polymer can also be one or more of polyurethane, polysiloxane, and polyphosphate. The lithium salt can also be one or more of lithium chloride, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(oxalate borate), lithium difluoro(oxalate borate), and lithium bis(difluorosulfonyl)imide. The organic solvent can also be one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethanol, methanol, carbon tetrafluoride, ethylene glycol, propionitrile, tributyl phosphate, chloroform, and ethyl acetate. Ionic liquids can also be 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, 1,3-bis(cyanomethyl)imidazolium chloride, 1,3-bis(cyanomethyl)imidazolium bis(pentafluoroethylsulfonyl)imide, 1-cyanomethyl-3-methylimidazolium chloride, 1-cyanomethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-3-methylimidazolium tricyanomethyl salt, 3-cyanopyridine hydrogen sulfate, 1,10-phenanthroline dihydrogen sulfate, 1-methyl-3-ethylimidazolium dicyanamide, 3-methyl-1-butylpyridine One or more of dicyanamide, 1-butyl-3-methylimidazole dihydrogen phosphate, 1-hexyl-3-methylimidazole dicyanamide, 1-butyl-3-methylimidazole hydrogen sulfate, 1-ethyl-3-methylimidazole tetrafluoroborate, 1-methyl-3-hexadecyl imidazole tetrafluoroborate, poly (1-butyl-4-vinylpyridine dicyanamide), polymerized p-phenylenediamine sulfate, 1-ethyl-3-methylimidazole dicyanamide, 1-cyano-3-methylimidazolyl chloride, 1-butyl-3-methylimidazole tetrachloroferrate, 1-butyl-3-methylimidazole tetrafluoroborate. The polymer porous membrane can also be prepared by phase inversion, stretching or thermally induced phase separation, and its matrix material can also be one or more of polyethylene, polyvinylidene fluoride, polyvinyl alcohol, polyurethane, polyetheretherketone, polyaniline, polystyrene, polyglycolic acid, polylactic acid, polycaprolactone and polyamide.
[0055] Moreover, the molar ratio of the structural unit of the ion conductive polymer to the lithium salt can also be 5:1, 40:1 or other ratios; the mass concentration of the ion conductive polymer can also be 0.01g / mL, 0.1g / mL, 0.2g / mL or other concentrations. The mass ratio of the ionic liquid to the ion conductive polymer can also be 2.5:1, 5:1 or other ratios. The stirring time can also be set to 9.5h, 16h, 24h or other durations. The thickness of the polymer porous membrane can also be 10μm, 160μm, 300μm or other thicknesses. The blast drying temperature can also be 25℃, 62℃, 100℃ or other temperatures, and the drying time can also be 6h, 9h, 12h or other durations. The vacuum drying temperature can also be 90℃, 110℃, 120℃ or other temperatures, and the drying time can also be 12h, 18h, 45h or other durations.
[0056] The electrolyte membrane prepared by the present invention is formed by a polymer porous membrane and an ion conductive polymer, a lithium salt, and an ionic liquid. That is, the electrolyte membrane is based on a polymer porous membrane 1, and a copolymer layer 2 formed by an ion conductive polymer, a lithium salt, and an ionic liquid is covered on the surface and pores of the substrate. The structure is as follows: Figure 2 shown.
[0057] The present invention is described by way of embodiments, but does not constitute a limitation to the present invention. With reference to the description of the present invention, other changes to the disclosed embodiments are easily conceivable to professionals in the field, and such changes should fall within the scope defined by the claims of the present invention.
Claims
1. A method for preparing a double-sided adhesive type adhesive polymer solid electrolyte membrane, characterized in that The following steps are involved: (1) dissolving an ion conductive polymer and a lithium salt in an organic solvent at a certain molar ratio to prepare a solution A; (2) adding an appropriate amount of ionic liquid to solution A and stirring for a certain period of time to obtain a uniform solution B; (3) adding solution B to a polymer porous membrane having a certain thickness to fully infiltrate the membrane; (4) The polymer porous membrane fully soaked with solution B is dried by air blowing for a period of time, and then dried under vacuum to obtain a double-sided adhesive-type adhesive polymer solid electrolyte membrane for lithium-ion batteries.
2. The method for preparing the double-sided adhesive type adhesive polymer solid electrolyte membrane according to claim 1, characterized in that: The ion conductive polymer described in step (1) is one or more of polyether, polycarbonate, polyurethane, polysiloxane and polyphosphate.
3. The method for preparing the double-sided adhesive type adhesive polymer solid electrolyte membrane according to claim 1, characterized in that: The lithium salt described in step (1) is one or more of lithium chloride, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(difluorosulfonylimide), and lithium bis(trifluoromethylsulfonylimide).
4. The method for preparing the double-sided adhesive type adhesive polymer solid electrolyte membrane according to claim 1, characterized in that: The molar ratio described in step (1) is the molar ratio of the structural unit of the ion conductive polymer to the lithium salt, ranging from (5 to 40):1; and the mass concentration of the ion conductive polymer is 0.01 to 0.2 g / mL.
5. The method for preparing the double-sided adhesive type adhesive polymer solid electrolyte membrane according to claim 1, characterized in that: The organic solvent described in step (1) is one or more of acetonitrile, acetone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, ethanol, methanol, carbon tetrafluoride, ethylene glycol, propionitrile, tributyl phosphate, chloroform, and ethyl acetate.
6. The method for preparing the double-sided adhesive type adhesive polymer solid electrolyte membrane according to claim 1, characterized in that: The step (2) of adding an appropriate amount of ionic liquid refers to adding the ionic liquid to the ion conductive polymer in a mass ratio of (1 to 5): 1, and stirring for 5 to 24 hours; and the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, 1,3-bis(cyanomethyl)imidazolium chloride, 1,3-bis(cyanomethylimidazolium bis(trifluoromethylsulfonyl)imide, 1,3-bis(cyanomethyl)imidazolium bis(pentafluoroethylsulfonyl)imide, 1-cyanomethyl-3-methylimidazolium chloride, 1-cyanomethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-butyl-3-methylimidazolium tricyanomethyl salt, 3-cyanopyridine hydrogen sulfate, 1 , 10-phenanthroline dihydrogensulfate, 1-methyl-3-ethylimidazole dicyanamide, 3-methyl-1-butylpyridine dicyanamide, 1-butyl-3-methylimidazole dihydrogenphosphate, 1-hexyl-3-methylimidazole dicyanamide, 1-butyl-3-methylimidazole hydrogensulfate, 1-ethyl-3-methylimidazole tetrafluoroborate, 1-methyl-3-hexadecylimidazole tetrafluoroborate, poly (1-butyl-4-vinylpyridine dicyanamide), polymerized p-phenylenediamine sulfate, 1-ethyl-3-methylimidazole dicyanamide, 1-cyano-3-methylimidazolyl chloride, 1-butyl-3-methylimidazole tetrachloroferrate, N,N-dimethyl-N-formyl ammonium bis (trifluoromethylsulfonyl) imide, 1-butyl-3-methylimidazole tetrafluoroborate or more.
7. The method for preparing the double-sided adhesive type adhesive polymer solid electrolyte membrane according to claim 1, characterized in that: The polymer porous membrane described in step (3) can be prepared by electrospinning, melt spinning, phase inversion, stretching or thermally induced phase separation, and the matrix material of the polymer porous membrane is one or more of polyethylene, polypropylene, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, polyurethane, polyetheretherketone, polyimide, polyaniline, polystyrene, polyglycolic acid, polylactic acid, polycaprolactone and polyamide.
8. The method for preparing the double-sided adhesive type adhesive polymer solid electrolyte membrane according to claim 1, characterized in that: The thickness of the polymer porous membrane in step (3) is 10 to 300 μm.
9. The method for preparing the double-sided adhesive type adhesive polymer solid electrolyte membrane according to claim 1, characterized in that: The blast drying temperature in step (4) is 25-100° C., and the drying time is 1-12 hours; the vacuum drying temperature is 60-120° C., and the drying time is 12-48 hours.
10. A double-sided adhesive type adhesive polymer solid electrolyte membrane prepared by the method according to any one of claims 1 to 9, characterized in that: The electrolyte membrane uses a polymer porous membrane as a matrix, and a copolymer layer formed by an ion conductive polymer, a lithium salt and an ionic liquid is covered on the surface and pores of the matrix.